2014
DOI: 10.5539/ass.v10n10p68
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Schooling, Public Health Programmes and Child Morbidity in Nigeria

Abstract: The role of investment in human resources and subsequent multiplier on the economic growth of any nation has been adequately addressed in the literature. Education, a major investment in human resources helps in improving the productivity of labour in the labour market and also in influencing children mental alertness and health outcomes. Maternal education and public health programmes have been found to impact positively on child morbidity in developed countries thereby contributing to the growth of any econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Since Caldwell’s seminal work [ 13 ], it has been maintained that maternal education is a critical determinant of child health [ 14 , 15 ]. Studies have found that maternal education[ 16 20 ], rather than paternal education [ 21 ], is associated with child health. On the other hand, other studies have investigated the impact of both parents’ education on child health [ 22 , 23 ], and compared each parent’s relative importance in child health [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since Caldwell’s seminal work [ 13 ], it has been maintained that maternal education is a critical determinant of child health [ 14 , 15 ]. Studies have found that maternal education[ 16 20 ], rather than paternal education [ 21 ], is associated with child health. On the other hand, other studies have investigated the impact of both parents’ education on child health [ 22 , 23 ], and compared each parent’s relative importance in child health [ 24 ].…”
Section: Introductionmentioning
confidence: 99%